2018
DOI: 10.1177/0003489418772067
|View full text |Cite
|
Sign up to set email alerts
|

Tracheoesophageal Prosthesis Use Is Associated With Improved Overall Quality of Life in Veterans With Laryngeal Cancer

Abstract: Using tracheoesophageal speech after total laryngectomy is associated with durable improvements in quality of life and functional outcomes in veterans. Tracheoesophageal voice restoration should be attempted whenever technically feasible in patients that meet the complex psychosocial and physical requirements to appropriately utilize TE speech.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Learning appropriate useful coping strategies is important for dealing with the new situation and affects the quality of life [100]. Speech rehabilitation should be carried out with a voice prosthesis whenever possible [109] and is crucial for the patient's quality of life [14]. It is problematic that the reduced quality of life due to functional damage and mental stress does not seem to improve with time, even after 10 years [107].…”
Section: Quality Of Life After Total Laryngectomymentioning
confidence: 99%
“…Learning appropriate useful coping strategies is important for dealing with the new situation and affects the quality of life [100]. Speech rehabilitation should be carried out with a voice prosthesis whenever possible [109] and is crucial for the patient's quality of life [14]. It is problematic that the reduced quality of life due to functional damage and mental stress does not seem to improve with time, even after 10 years [107].…”
Section: Quality Of Life After Total Laryngectomymentioning
confidence: 99%
“…In both methods of voice rehabilitation, an internal substitute sound source is produced in the pharyngoesophageal segment. Many studies have reported that tracheoesophageal speech (TES) provides a good quality of speech and represents an excellent means of communication 1113. However, it is difficult to determine the most effective rehabilitation method in terms of both objective good quality of voice and greater satisfaction for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to determine the most effective rehabilitation method in terms of both objective good quality of voice and greater satisfaction for the patient. Few studies12,13 have considered the correlation between quality of voice, assessed by using acoustic analysis, and patients’ perception of their rehabilitated voice. Therefore, this study aimed to determine the acoustic quality of the rehabilitated voice, achieved with ES and TES, and its impacts on patients’ perceptions of their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case for major enlargements of the tracheo-esophageal fistulae that occur in less than 5% of patients but can require highly complex surgical reconstruction [52,53]. However, with an experienced multidisciplinary team, the advantages of using TEP far outweigh their drawbacks [50,54]. Currently, there is no consensus that exists with regard to the timing of performing TEP, and the decision to perform a primary (at time of TL) or secondary TEP has mostly been based on physician preference [10,55].…”
Section: Functional Results and Quality Of Life After Total Laryngectomymentioning
confidence: 99%